Interactive Plan Hints for Query Optimization - Bruno, Nicolas; Chaudhuri, Surajit; Ramamurthy, Ravi (SIGMOD, 2009)
Commercial database systems expose query hints to fix poor plans produced by the query optimizer. However, current query hints are not flexible enough to deal with a variety of non-trivial scenarios, and can be at times cumbersome for DBAs to interact with. In this demonstration we present a framework that enables visual specification of hints to influence the optimizer to pick better plans. Our framework goes considerably beyond existing hinting mechanisms and significantly improves the usability of such functionality.